ANALYSIS OF STUDENTS' DIFFICULTIES IN SOLVE STORY QUESTIONS IN INDONESIAN LANGUAGE SUBJECTS IN PRIMARY SCHOOLS: ANALYSIS OF STUDENTS' DIFFICULTIES IN SOLVE STORY QUESTIONS IN INDONESIAN LANGUAGE SUBJECTS IN PRIMARY SCHOOLS - cica cintya; Anggy Giri Prawiyogi; sinta mariana dewi (Jurnal Cakrawala Pendas, 2024)
This study aims to analyze students' difficulties in solving story problems in the subject of Bahasa Indonesia at the Elementary School level. It was conducted on third-grade students at SDN Pangulah Utara during the academic year 2023/2024. The research method used was qualitative with a focus on problem research. Data were collected through observation, interviews with Bahasa Indonesia teachers, tests, and documentation. The results showed that the majority of students experienced difficulties in understanding and solving story problems, with most of them categorized as moderate and low. Factors such as vocabulary understanding, sentence structure, and understanding the context of the story influenced students' difficulties in solving story problems. Bahasa Indonesia teachers acknowledged constraints in teaching story problem materials, especially related to limited teaching time. Therefore, efforts should be made to improve students' understanding abilities in story problems, such as enhancing vocabulary understanding, explaining sentence structures, helping students understand the context of the story, using varied teaching methods, providing sufficient teaching time, conducting teacher training, and developing engaging and interactive learning media. Thus, it is hoped that students' comprehension abilities in story problems can improve, enabling them to understand stories better and answer questions more accurately.